Laminate and method for manufacturing the same
Patent Information
- Application Number
- JP2022093004
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-08
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2042-06-08
AI Technical Summary
Conventional thermally conductive adhesives used in LSIs experience increased contact resistance and decreased thermal conductivity when forming a layer between copper and silicon base materials.
A laminate structure comprising a first and second thermally conductive layer with specific particle size ratios and low-melting point metal particles, along with a curing component and agent, is used to enhance thermal conductivity and reduce thermal resistance.
The laminate achieves high thermal conductivity and low thermal resistance by increasing contact area and forming a network of alloyed metal particles, improving heat dissipation in electronic devices.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a laminate and a method for manufacturing the laminate. [Background technology]
[0002] In LSIs and other electronic devices, if the LSI itself is exposed to high temperatures for a long period of time due to heat generated by the elements used, this may lead to malfunction or failure. For this reason, thermally conductive materials are widely used to prevent the temperature of LSIs and other devices from rising. The thermally conductive materials can prevent the temperature of the device from rising by diffusing the heat generated by the elements or by conducting it to a heat dissipation member for release outside the system, such as to the atmosphere.
[0003] When metals or ceramics are used as such thermally conductive materials, problems such as difficulty in reducing weight, poor processability, and low flexibility have been proposed. Therefore, various thermally conductive materials have been proposed that use polymeric materials such as resins or rubbers as a base material. For example, a thermally conductive adhesive has been proposed that includes a thermosetting adhesive containing a curing component and a curing agent for the curing component, and a metal filler dispersed in the thermosetting adhesive, the metal filler containing silver powder and solder powder, the solder powder having a melting temperature lower than the thermal curing temperature of the thermally conductive adhesive and reacting with the silver powder under the thermal curing conditions of the thermosetting adhesive to form a high-melting-point solder alloy having a melting point higher than the melting temperature of the solder powder, the curing agent having flux activity with respect to the metal filler, the curing component being a glycidyl ether-type epoxy resin, and the curing agent being a monoanhydride of a tricarboxylic acid (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5796242 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the conventional technology described in Patent Document 1, when a thermally conductive layer made of a thermally conductive adhesive is formed between a copper substrate and a silicon substrate, the contact resistance with the silicon interface increases, resulting in a decrease in thermal conductivity.
[0006] The present invention aims to solve the above-mentioned problems in the prior art and to achieve the following object: That is, the present invention aims to provide a laminate that can achieve high thermal conductivity and low thermal resistance, and a method for manufacturing the laminate. [Means for solving the problem]
[0007] The means for solving the above problems are as follows: <1> A substrate; a first thermally conductive layer on the base material, the first thermally conductive layer including a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles; a second thermally conductive layer on the first thermally conductive layer, the second thermally conductive layer including a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles; and a portion of the first thermally conductive particles contained in the first thermally conductive layer and a portion of the second thermally conductive particles contained in the second thermally conductive layer are in contact with each other, and the volume average particle size of the first thermally conductive particles is smaller than the volume average particle size of the second thermally conductive particles; The laminate is characterized in that the substrate contains at least one material selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics. <2> the ratio (A:B) of the volume average particle size A of the first thermally conductive particles to the volume average particle size B of the second thermally conductive particles is 1:2 to 1:50; <1> 1. The laminate according to claim 1. <3> The first thermally conductive particles have a volume average particle size of 0.3 μm or more and 30 μm or less. <1> from <2> The laminate according to any one of the above items. <4> The second thermally conductive particles have a volume average particle size of 1 μm or more and 100 μm or less. <1> from <3> The laminate according to any one of the above items. <5> The first and second thermally conductive particles are at least one of copper particles, silver-coated particles, and silver particles. <1> from <4> The laminate according to any one of the above items. <6> The low-melting-point metal particles contain Sn and at least one selected from Bi, Ag, Cu, and In. <1> from <5> The laminate according to any one of the above items. <7> the curing agent has flux activity with respect to the first and second thermally conductive particles; <1> from <6> The laminate according to any one of the above items. <8> The curing component is at least one of an oxirane ring compound and an oxetane compound. <1> from <7> The laminate according to any one of the above items. <9> a third thermally conductive layer between the first thermally conductive layer and the second thermally conductive layer; <1> from <8> The laminate according to any one of the above items. <10> the third thermally conductive layer is copper foil; <9> 1. The laminate according to claim 1. <11> a facing substrate on the second thermally conductive layer, the facing substrate facing the substrate; the opposing substrate contains at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof; <1> from <10> The laminate according to any one of the above items. <12> a first thermally conductive layer forming step of forming a first thermally conductive layer on the base material, the first thermally conductive layer including a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles; a second thermally conductive layer forming step of forming a second thermally conductive layer on the first thermally conductive layer, the second thermally conductive layer including a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles; Including, The method for producing a laminate is characterized in that the substrate contains at least one material selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics. [Effects of the Invention]
[0008] According to the present invention, it is possible to solve the above-mentioned problems in the prior art, achieve the above-mentioned object, and provide a laminate that can realize high thermal conductivity and low thermal resistance, and a method for manufacturing the laminate. [Brief explanation of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic view showing an example of a laminate according to the first embodiment. [Figure 2] FIG. 2 is a schematic view showing an example of a laminate according to the second embodiment. [Figure 3] FIG. 3 is a schematic cross-sectional view showing an example of a heat dissipation structure used in the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0010] (Laminate) The laminate of the present invention has a substrate, a first thermally conductive layer, a second thermally conductive layer, and preferably a third thermally conductive layer and an opposing substrate, and may further have other members as necessary.
[0011] In the present invention, a first thermally conductive layer and a second thermally conductive layer are provided on a substrate in this order, a portion of the first thermally conductive particles are in contact with a portion of the second thermally conductive particles, and the volume average particle size of the first thermally conductive particles is smaller than the volume average particle size of the second thermally conductive particles. Therefore, even in the case of a substrate having poor solder wettability and made of at least one material selected from silicon, aluminum, tungsten, molybdenum, glass, molded resin, stainless steel, and ceramics, the increased contact area can significantly improve thermal conductivity.
[0012] <Base material> The shape, structure, size, material, etc. of the substrate are not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape of the substrate include a plate shape, a sheet shape, etc. Examples of the structure of the substrate include a single-layer structure, a laminated structure, etc. The size of the substrate can be appropriately selected depending on the application, etc. The substrate is made of a material that is difficult for solder to wet, and includes at least one selected from silicon, aluminum, tungsten, molybdenum, glass, mold resin, stainless steel, and ceramics. Examples of the ceramics include aluminum nitride, silicon carbide, alumina, and gallium nitride. Examples of the mold resin include epoxy resin, silicone resin, urethane resin, and acrylic resin. The average thickness of the substrate is not particularly limited and can be appropriately selected depending on the purpose. The substrate may be the heat generating element (electronic component) itself in the heat dissipation structure.
[0013] <First thermal conduction layer> The first thermally conductive layer is preferably formed on the substrate and in contact with the substrate. The first thermally conductive layer contains a curable component, a curing agent for curing the curable component, first thermally conductive particles, and low-melting-point metal particles, and may further contain other components as required.
[0014] -Curing component- As the curing component, it is preferable to use at least one of an oxirane ring compound and an oxetane compound.
[0015] --Oxirane ring compounds-- The oxirane ring compound is a compound having an oxirane ring, and examples thereof include epoxy resins. The epoxy resin is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A type epoxy resins, trisphenol type epoxy resins, tetraphenol type epoxy resins, phenol-xylylene type epoxy resins, naphthol-xylylene type epoxy resins, phenol-naphthol type epoxy resins, phenol-dicyclopentadiene type epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. These may be used alone or in combination of two or more.
[0016] --Oxetane compounds-- The oxetane compound is a compound having an oxetanyl group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound may be a monofunctional oxetane compound having only one oxetanyl group, or may be a polyfunctional oxetane compound having two or more oxetanyl groups.
[0017] The oxetane compound is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4 -bis(3-ethyl-3-oxetanylmethoxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), etc. These may be used alone or in combination of two or more.
[0018] As the oxetane compound, commercially available products can be used, and examples of the commercially available products include the "Aron Oxetane (registered trademark)" series sold by Toagosei Co., Ltd. and the "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd.
[0019] Among the above oxirane ring compounds and oxetane compounds, glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, phenol-dicyclopentadiene type epoxy resins, bisphenol A type epoxy resins, aliphatic epoxy resins, and 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP) are preferred.
[0020] The content of the curing component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by mass to 60% by mass relative to the total amount of the first thermally conductive layer.
[0021] - Hardener - The curing agent is a curing agent corresponding to the curing component, and examples thereof include polyaddition-type curing agents such as acid anhydride-based curing agents, aliphatic amine-based curing agents, aromatic amine-based curing agents, phenol-based curing agents, and mercaptan-based curing agents, and catalyst-type curing agents such as imidazole. These may be used alone or in combination of two or more. Among these, acid anhydride-based curing agents are preferred. When the curing component is an epoxy resin, the acid anhydride-based curing agent is preferred because it does not generate gas during thermal curing, can achieve a long pot life when mixed with the epoxy resin, and can achieve a good balance between the electrical properties, chemical properties, and mechanical properties of the resulting cured product. Examples of the acid anhydride curing agent include cyclohexane-1,2-dicarboxylic acid anhydride and mono-acid anhydrides of tricarboxylic acids. Examples of the mono-acid anhydrides of tricarboxylic acids include cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride.
[0022] The curing agent preferably has flux activity, as this improves the wettability of the molten low-melting-point metal particles to the thermally conductive particles. Examples of methods for imparting flux activity to the curing agent include introducing protonic acid groups, such as carboxyl groups, sulfonyl groups, and phosphate groups, into the curing agent by known methods. Among these, the introduction of carboxyl groups is preferred in terms of reactivity with the epoxy resin or oxetane compound used as the curing component. Examples of such groups include carboxyl-containing organic acids, such as glutaric acid and succinic acid. Alternatively, compounds modified from glutaric anhydride or succinic anhydride, or metal salts of organic acids, such as silver glutarate, may also be used.
[0023] The content of the curing agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1% by mass or more and 30% by mass or less with respect to the total amount of the first thermally conductive layer.
[0024] The molar equivalent ratio (C / D) between the curing component C and the curing agent D varies depending on the types of the curing component and curing agent used and cannot be generally defined, but is preferably 0.5 or more and 3 or less, more preferably 0.5 or more and 2 or less, and even more preferably 0.7 or more and 1.5 or less. When the equivalent ratio (C / D) is 0.5 or more and 3 or less, there is an advantage that the low-melting-point metal particles can be sufficiently melted to form a network when the thermal conductive composition is thermally cured.
[0025] -First heat-conducting particle- The first thermally conductive particles are preferably at least one of copper particles, silver-coated particles, and silver particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the first thermally conductive particles is not particularly limited and can be appropriately selected depending on the purpose. Examples include spherical, flat, granular, and needle-like shapes. The volume average particle size of the first thermally conductive particles is preferably 0.3 μm to 30 μm, more preferably 0.5 μm to 10 μm. When the volume average particle size of the thermally conductive particles is 0.3 μm to 30 μm, the volume ratio of the first thermally conductive particles to the low-melting-point metal particles can be increased, thereby achieving high thermal conductivity and low thermal resistance. The volume average particle size can be measured, for example, by a laser diffraction / scattering particle size distribution measuring device (product name: Microtrac MT3300EXII).
[0026] -Low melting point metal particles- As the low melting point metal particles, solder particles as specified in JIS Z3282-1999 are preferably used. Examples of the solder particles include Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. These may be used alone or in combination of two or more. Among these, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, and Sn-Bi based solder particles, Sn-Bi-Ag based solder particles, Sn-Ag-Cu based solder particles, and Sn-In based solder particles are more preferred.
[0027] The shape of the low melting point metal particles is not particularly limited and can be appropriately selected depending on the purpose. Examples include spherical, flat, granular, and needle-like shapes. The melting point of the low-melting-point metal particles is preferably 100°C or higher and 250°C or lower, and more preferably 120°C or higher and 200°C or lower. It is preferable that the melting point of the low-melting-point metal particles is lower than the thermal curing temperature of the first thermal conductive composition, because the low-melting-point metal particles melted in the cured product of the first thermal conductive composition can form a network (a continuous metal phase) via the first thermal conductive particles, thereby achieving high thermal conductivity and low thermal resistance. The low-melting-point metal particles react with the thermally conductive particles under the conditions for thermal curing of the first thermally conductive composition to form an alloy with a higher melting point than the low-melting-point metal particles, thereby preventing melting at high temperatures and improving reliability and heat resistance of the cured product of the first thermally conductive composition. The thermal curing treatment of the first thermal conductive composition is carried out, for example, at a temperature of 150° C. to 200° C. for 30 minutes to 2 hours.
[0028] The volume average particle size of the low-melting-point metal particles is preferably 10 μm or less, more preferably 1 μm or more and 5 μm or less. When the volume average particle size of the low-melting-point metal particles is 10 μm or less, the volume ratio of the low-melting-point metal particles to the thermally conductive particles can be reduced, thereby realizing high thermal conductivity and low thermal resistance of the first thermally conductive layer. The volume average particle size of the low-melting point metal particles can be measured in the same manner as the volume average particle size of the first thermally conductive particles.
[0029] The volume average particle size of the first thermally conductive particles is larger than the volume average particle size of the low-melting point metal particles, and the volume average particle size ratio (A / B) of the thermally conductive particles A to the low-melting point metal particles B is preferably 2 or more, more preferably 3 or more, and even more preferably 5 or more. The upper limit of the volume average particle size ratio (A / B) is preferably 20 or less, more preferably 10 or less. By using low-melting-point metal particles with a smaller volume average particle size than the first thermally conductive particles, the thermally conductive particles become the main component in the first thermally conductive composition, and the low-melting-point metal particles present between the first thermally conductive particles melt when heated and alloy with the first thermally conductive particles to form a network, thereby achieving high thermal conductivity and low thermal resistance.
[0030] The volume ratio (A / B) of the first thermally conductive particles A to the low-melting point metal particles B in the first thermally conductive layer is preferably at least 1, more preferably at least 1.5, and even more preferably at least 2. The upper limit of the volume ratio (A / B) is preferably at most 5, more preferably at most 4, and even more preferably at most 3. When the volume ratio (A / B) is 1 or more, the volume ratio of the thermally conductive particles, which have a larger volume average particle size than the low-melting-point metal particles, is high, which can suppress the flow of the molten low-melting-point metal particles.In addition, since separation is unlikely to occur even at interfaces that are difficult for the low-melting-point metal particles to wet (e.g., silicon), the influence of the interface material can be suppressed, and the selectivity of the interface material is improved.
[0031] -polymer- The first thermally conductive layer preferably contains a polymer to impart flexibility and the like. The polymer is not particularly limited and can be appropriately selected depending on the purpose. Examples include polymers having at least one structure selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polyamide structure, and a polycarbonate structure in the molecule. The content of the polymer is preferably from 1 to 50% by mass, more preferably from 1 to 30% by mass, and even more preferably from 1 to 10% by mass, based on the total amount of the first thermally conductive layer.
[0032] -Other ingredients- The first thermally conductive layer may contain other components as long as the effects of the present invention are not impaired. The other components are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include non-metallic thermally conductive particles (e.g., aluminum nitride, alumina, carbon fiber, etc.), additives (e.g., antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.), etc.
[0033] The first thermally conductive composition can be prepared by uniformly mixing the curing component, the curing agent, the first thermally conductive particles, the low-melting-point particles, the polymer, and, if necessary, other components, using a conventional method.
[0034] The average thickness of the first thermally conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 μm or more and 100 μm or less, and more preferably 5 μm or more and 50 μm or less.
[0035] <Second thermal conduction layer> The second thermally conductive layer contains a curable component, a curing agent that cures the curable component, second thermally conductive particles, and low-melting-point metal particles, and may further contain other components as required.
[0036] -Second heat conducting particle- The second thermally conductive particles are preferably at least one of copper particles, silver-coated particles, and silver particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the second thermally conductive particles is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include spherical, flat, granular, and acicular shapes. It is necessary that a portion of the first thermally conductive particles contained in the first thermally conductive layer and a portion of the second thermally conductive particles contained in the second thermally conductive layer are in contact with each other, and that the volume average particle size of the first thermally conductive particles is smaller than that of the second thermally conductive particles. If the volume average particle size of the first thermally conductive particles is larger than that of the second thermally conductive particles, the thermal conductivity of the laminate may decrease. The ratio (A:B) of the volume average particle size A of the first thermally conductive particles to the volume average particle size B of the second thermally conductive particles is preferably 1:2 to 1:50, and more preferably 1:10 to 1:40. The volume average particle size of the second thermally conductive particles is preferably 1 μm to 100 μm, more preferably 10 μm to 70 μm, and even more preferably 10 μm to 50 μm. When the volume average particle size of the second thermally conductive particles is 1 μm to 100 μm, high thermal conductivity and low thermal resistance can be achieved. The volume average particle size of the second thermally conductive particles can be measured in the same manner as the volume average particle size of the first thermally conductive particles.
[0037] The hardening components, hardeners, low-melting-point metal particles, polymers, and other components in the second thermally conductive layer are similar to the hardening components, hardeners, low-melting-point metal particles, polymers, and other components in the first thermally conductive layer described above, and therefore details thereof will be omitted.
[0038] The average thickness of the second thermally conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 20 μm or more and 300 μm or less, and more preferably 50 μm or more and 200 μm or less.
[0039] <Third thermal conductive layer> The third thermally conductive layer is formed between the first thermally conductive layer and the second thermally conductive layer, and the third thermally conductive layer may be a single layer or may be a multi-layer structure of two or more layers. The third thermally conductive layer is preferably a copper foil in terms of thermal conductivity. The average thickness of the third thermally conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 5 μm or more and 200 μm or less, and more preferably 10 μm or more and 100 μm or less.
[0040] <Facing substrate> The opposing substrate is disposed opposite the substrate, and its shape, structure, size, material, etc. are not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape of the opposing substrate include a plate shape, a sheet shape, etc. Examples of the structure of the opposing substrate include a single-layer structure, a laminated structure, etc. The size of the opposing substrate can be appropriately selected depending on the application, etc. The material of the opposing substrate is a material that is easily wetted by solder, and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the purpose. The opposing substrate may be the heat spreader itself in the heat dissipation structure.
[0041] <Other materials> The other members are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a protective layer.
[0042] (Method of manufacturing laminate) The method for producing a laminate of the present invention includes a first thermally conductive layer forming step and a second thermally conductive layer forming step, and may further include other steps as necessary.
[0043] <First thermal conductive layer forming step> The first thermally conductive layer forming step is a step of forming a first thermally conductive layer on the substrate, the first thermally conductive layer containing a curing component, a curing agent that cures the curing component, first thermally conductive particles, and low-melting point metal particles. The substrate includes at least one material selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics. The hardening component, hardening agent, first thermally conductive particles, and low-melting-point metal particles are the same as the hardening component, hardening agent, first thermally conductive particles, and low-melting-point metal particles contained in the first thermally conductive layer, and therefore their description will be omitted.
[0044] Examples of methods for forming the first thermally conductive layer include (1) a method of applying a first thermally conductive composition containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles onto a substrate and curing the composition, and (2) a method of forming a cured material layer containing a cured product of the first thermally conductive composition containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles on a support with a release layer, and then transferring the cured material layer onto the substrate. In the method (2), the support is peeled off when the cured material layer is transferred onto the substrate. Examples of methods for applying the first thermally conductive composition in (1) to the substrate include inkjet coating, blade coating, gravure coating, gravure offset coating, bar coating, roll coating, knife coating, air knife coating, comma coating, U comma coating, AKKU coating, smoothing coating, microgravure coating, reverse roll coating, four-roll coating, five-roll coating, dip coating, curtain coating, slide coating, and die coating.
[0045] <Second thermal conductive layer forming step> The second thermally conductive layer forming step is a step of forming a second thermally conductive layer on the first thermally conductive layer, the second thermally conductive layer containing a curing component, a curing agent that hardens the curing component, second thermally conductive particles, and low-melting point metal particles. The hardening component, the hardening agent, the second thermally conductive particles, and the low-melting-point metal particles are the same as the hardening component, the hardening agent, the second thermally conductive particles, and the low-melting-point metal particles contained in the second thermally conductive layer, and therefore their description will be omitted.
[0046] Examples of methods for forming the second thermally conductive layer include (1) applying a second thermally conductive composition containing a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles onto the first thermally conductive layer and curing it, and (2) forming a cured material layer containing a cured product of the second thermally conductive composition containing the curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles on a support with a release layer, and transferring the cured material layer onto the first thermally conductive layer. In the method (2), the support is peeled off when the cured material layer is transferred onto the first thermally conductive layer. Examples of methods for applying the second thermally conductive composition in (1) to the first thermally conductive layer include inkjet coating, blade coating, gravure coating, gravure offset coating, bar coating, roll coating, knife coating, air knife coating, comma coating, U-comma coating, AKKU coating, smoothing coating, microgravure coating, reverse roll coating, four-roll coating, five-roll coating, dip coating, curtain coating, slide coating, and die coating.
[0047] <Other processes> The other steps are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a third thermal conductive layer forming step.
[0048] Here, an embodiment of the laminate of the present invention will be described in detail with reference to the drawings. In each drawing, the same components are denoted by the same reference numerals, and duplicated explanations may be omitted. Furthermore, the number, position, shape, etc. of the following components are not limited to the present embodiment, and may be any number, position, shape, etc. that is preferable for implementing the present invention.
[0049] First Embodiment Fig. 1 is a schematic diagram showing an example of a laminate according to the first embodiment. The laminate 10 in Fig. 1 has a first thermally conductive layer 12 containing first thermally conductive particles 15 on a substrate 11, a second thermally conductive layer 13 containing second thermally conductive particles 16 on the first thermally conductive layer 12, and an opposing substrate 14 on the second thermally conductive layer 13. A portion of the first thermally conductive particles 15 contained in the first thermally conductive layer 12 and a portion of the second thermally conductive particles 16 contained in the second thermally conductive layer 13 are in contact with each other, and the volume average particle size of the first thermally conductive particles is smaller than the volume average particle size of the second thermally conductive particles.
[0050] <Second embodiment> Fig. 2 is a schematic diagram showing an example of a laminate according to the second embodiment. The laminate 20 in Fig. 2 has a first thermally conductive layer 12 containing first thermally conductive particles 15 on a substrate 11, a third thermally conductive layer 17 made of copper foil on the first thermally conductive layer 12, a second thermally conductive layer 13 containing second thermally conductive particles 16 on the third thermally conductive layer 17, and an opposing substrate 14 on the second thermally conductive layer 13. A portion of the first thermally conductive particles 15 contained in the first thermally conductive layer 12 and a portion of the second thermally conductive particles 16 contained in the second thermally conductive layer 13 are in contact with each other via the third thermally conductive layer 17, and the volume average particle size of the first thermally conductive particles is smaller than the volume average particle size of the second thermally conductive particles.
[0051] The laminate of the present invention can be suitably used, for example, as a thermal interface material (TIM) that fills the minute gap between a heat source such as an LSI and a heat sink, thereby allowing heat to flow smoothly between the two, or when bonding a heat dissipation substrate on which an LED chip or an IC chip is mounted to a heat sink to form a power LED module or a power IC module. Here, the power LED module is available in a wire bonding mounting type and a flip chip mounting type, and the power IC module is available in a wire bonding mounting type.
[0052] The heat dissipation structure used in the present invention comprises a heat generating body, the laminate of the present invention, and a heat dissipation member.
[0053] The heating element is not particularly limited and can be appropriately selected depending on the purpose. Examples include electronic components such as a CPU (Central Processing Unit), an MPU (Micro Processing Unit), and a GPU (Graphics Processing Unit).
[0054] The heat dissipation member is not particularly limited as long as it is a structure that dissipates heat generated by electronic components (heat generating elements), and can be appropriately selected depending on the purpose. Examples include a heat spreader, a heat sink, a vapor chamber, and a heat pipe. The heat spreader is a member for efficiently transferring heat from the electronic component to other components. The material of the heat spreader is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include copper and aluminum. The heat spreader is usually in a flat plate shape. The heat sink is a member for releasing heat from the electronic component into the air. The material of the heat sink is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include copper and aluminum. The heat sink has, for example, a plurality of fins. The heat sink has, for example, a base portion and a plurality of fins extending in a non-parallel direction (for example, a direction perpendicular to) one surface of the base portion. The heat spreader and the heat sink are generally solid structures with no internal voids. The vapor chamber is a hollow structure. A volatile liquid is sealed in the internal space of the hollow structure. Examples of the vapor chamber include a hollow heat spreader and a hollow plate-like structure similar to the heat sink. The heat pipe is a hollow structure having a cylindrical, approximately cylindrical, or flattened cylindrical shape, and a volatile liquid is sealed in the internal space of the hollow structure.
[0055] Here, Fig. 3 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates heat generated by an electronic component 3 such as a semiconductor element, and as shown in Fig. 3, is fixed to a main surface 2a of the heat spreader 2 facing the electronic component 3, and is sandwiched between the electronic component 3 and the heat spreader 2. In addition, the thermally conductive sheet 1 is sandwiched between the heat spreader 2 and a heat sink 5.
[0056] The heat spreader 2 is formed, for example, in the shape of a rectangular plate, and has a main surface 2a facing the electronic component 3 and side walls 2b erected along the outer periphery of the main surface 2a. The heat spreader 2 has a thermally conductive sheet 1 provided on the main surface 2a surrounded by the side walls 2b, and a heat sink 5 provided on the other surface 2c opposite the main surface 2a via the thermally conductive sheet 1. The higher the thermal conductivity of the heat spreader 2, the lower the thermal resistance and the more efficiently it absorbs heat from the electronic component 3, such as a semiconductor element. Therefore, the heat spreader 2 can be formed using, for example, copper or aluminum, which have good thermal conductivity.
[0057] The electronic component 3 is, for example, a semiconductor element such as a BGA, and is mounted on the wiring board 6. The tip surface of the side wall 2b of the heat spreader 2 is also mounted on the wiring board 6, so that the side wall 2b surrounds the electronic component 3 at a predetermined distance. By providing the laminate 7 of the present invention on the main surface 2 a of the heat spreader 2 , a heat dissipation member that absorbs heat generated by the electronic component 3 and dissipates the heat from the heat sink 5 is formed. [Example]
[0058] Examples of the present invention will be described below, but the present invention is not limited to these examples in any way.
[0059] (Examples 1 to 5, Comparative Examples 1 to 3, and Reference Example 1) <Preparation of Thermally Conductive Composition> The compositions and contents shown in Tables 1 to 3 were mixed uniformly using a stirring device (Awatori Rentaro Automatic Revolving Mixer, manufactured by Thinky Corporation) to prepare a first thermally conductive composition and a second thermally conductive composition. The contents of each component in Tables 1 to 3 are in parts by mass.
[0060] <Formation of laminate> Next, in Examples 1 to 5 and Comparative Example 3, a first thermally conductive composition was applied to a 30 mm × 30 mm × 2 mm substrate (silicon) according to the descriptions in Tables 1 to 3, and then a second thermally conductive composition was applied to the first thermally conductive layer. A 30 mm × 30 mm × 2 mm opposing substrate (copper) was laminated on top of this second thermally conductive composition, and the resultant was heated at 150°C for 60 minutes to harden, thereby forming a laminate having a first thermally conductive layer with an average thickness of 10 μm and a second thermally conductive layer with an average thickness of 70 μm. In Example 2, a copper foil having an average thickness of 30 μm was used as the third thermally conductive layer. In Reference Example 1 and Comparative Example 1, except that the first thermally conductive composition was not used, laminates were formed in the same manner as in Examples 1 to 5 and Comparative Example 3. In Reference Example 1, a 30 mm x 30 mm x 2 mm base material (copper) was used instead of the 30 mm x 30 mm x 2 mm base material (silicon). In Comparative Example 2, a laminate was formed in the same manner as in Examples 1 to 5 and Comparative Example 3, except that the second thermally conductive composition was not used.
[0061] Next, the thermal impedance and thermal conductivity of each of the obtained laminates were evaluated as follows. The results are shown in Tables 1 to 3.
[0062] <Thermal impedance> The thermal resistance (℃·cm) of each laminate was measured using a method in accordance with ASTM-D5470. 2 The thermal resistance of the cured product was calculated by subtracting the thermal resistance of the substrate and the opposing substrate from the result, and the thermal impedance (Kmm 2 / W) was calculated.
[0063] <Thermal conductivity> The thermal resistance (℃·cm) of each laminate was measured using a method in accordance with ASTM-D5470. 2 The thermal resistance of the cured product was calculated by subtracting the thermal resistance of the substrate and the opposing substrate from the result, and the thermal conductivity (W / m K) was calculated from this thermal resistance and the thickness of the cured product, and the thermal conductivity was evaluated according to the following criteria. [Evaluation criteria] ◎: Thermal conductivity is 15 W / m K or more 〇: Thermal conductivity is 10 W / m K or more and less than 15 W / m K ×: Thermal conductivity is less than 10 W / m K
[0064] [Table 1]
[0065] [Table 2]
[0066] [Table 3]
[0067] Details of each component in Tables 1 to 3 are as follows.
[0068] -Curing component- *OXBP: 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl manufactured by Ube Industries, Ltd.
[0069] - Hardener - *Polycarboxylic acid, synthesized by Dexerials Corporation
[0070] -Low melting point metal particles (solder particles)- *Sn 58 Bi 42 Manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size Dv: 4 μm, melting point 139°C
[0071] -First heat-conducting particle- *First thermally conductive particles 1: Ag particles, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm *First thermally conductive particles 2: Ag-coated Cu particles, manufactured by Fukuda Metal Foil and Powder Co., Ltd., volume average particle size Dv: 5 μm *First thermally conductive particles 3: Ag-coated Cu particles, manufactured by Fukuda Metal Foil and Powder Co., Ltd., volume average particle size Dv: 40 μm
[0072] -Second heat conducting particle- *Second thermal conductive particles 1: Ag-coated Cu particles, manufactured by Fukuda Metal Foil and Powder Co., Ltd., volume average particle size Dv: 40 μm *Second thermal conductive particles 2: Cu particles, manufactured by Fukuda Metal Foil and Powder Co., Ltd., volume average particle size Dv: 40 μm *Second thermally conductive particles 3: Ag particles, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm
[0073] -polymer- *M1276: Polyamide compound manufactured by Arkema Co., Ltd. [Industrial Applicability]
[0074] The laminate of the present invention can achieve high thermal conductivity and low thermal resistance as a thermal interface material (TIM), and is therefore suitable for use in, for example, the periphery of various electrical devices such as CPUs, MPUs, power transistors, LEDs, and laser diodes, where temperature can adversely affect the efficiency and lifespan of element operation. [Explanation of symbols]
[0075] 1. Thermal conductive sheet 2 heat spreaders 2a Main surface 3 Heat generating elements (electronic components) 3a Top side 5 Heatsink 6. Wiring board 7 Laminate 10 Laminate 11 Base material 12 First thermally conductive layer 13 Second thermally conductive layer 14 Opposing substrate 15 First heat conducting particles 16 Secondary heat conducting particles 17 Third heat conducting layer 20 laminate
Claims
1. A substrate; a first thermally conductive layer on the base material, the first thermally conductive layer including a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles; a second thermally conductive layer on the first thermally conductive layer, the second thermally conductive layer including a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles; and a portion of the first thermally conductive particles contained in the first thermally conductive layer and a portion of the second thermally conductive particles contained in the second thermally conductive layer are in contact with each other, and a volume average particle size of the first thermally conductive particles is smaller than a volume average particle size of the second thermally conductive particles; A laminate, wherein the substrate comprises at least one material selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.
2. 2. The laminate according to claim 1, wherein a ratio (A:B) of a volume average particle size A of the first thermally conductive particles to a volume average particle size B of the second thermally conductive particles is 1:2 to 1:
50.
3. The laminate according to claim 1 , wherein the first thermally conductive particles have a volume average particle size of 0.3 μm or more and 30 μm or less.
4. The laminate according to claim 1 , wherein the second thermally conductive particles have a volume average particle size of 1 μm or more and 100 μm or less.
5. The laminate according to claim 1 , wherein the first and second thermally conductive particles are at least one of copper particles, silver-coated particles, and silver particles.
6. The laminate according to claim 1 , wherein the low-melting-point metal particles contain Sn and at least one selected from the group consisting of Bi, Ag, Cu, and In.
7. The laminate according to claim 1 , wherein the curing agent has flux activity with respect to the first and second thermally conductive particles.
8. The laminate according to claim 1 , wherein the curing component is at least one of an oxirane ring compound and an oxetane compound.
9. The laminate according to claim 1 , further comprising a third thermally conductive layer between the first thermally conductive layer and the second thermally conductive layer.
10. 10. The laminate of claim 9, wherein the third thermally conductive layer is copper foil.
11. a facing substrate on the second thermally conductive layer, the facing substrate facing the substrate; 3. The laminate according to claim 1, wherein the opposing substrate comprises at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.
12. a first thermally conductive layer forming step of forming a first thermally conductive layer on the base material, the first thermally conductive layer including a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles; a second thermally conductive layer forming step of forming a second thermally conductive layer on the first thermally conductive layer, the second thermally conductive layer including a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles; Including, 10. A method for producing a laminate, wherein the substrate comprises at least one material selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.